Near miss Neonatal: integrative review (Research, Society and Development, 2020)
To investigate in scientific publications the evidence on the use / application of neonatal near miss. Integrative literature review in the National Library of Medicine (MEDLINE/PubMed), Medical Literature Analysis and Retrieval System Online (MEDLINE/EBSCO), Latin American and Caribbean Literature in Health Sciences (LILACS); Science Direct (ELSEVIER), and the Scientific Electronic Electronic Librery Online (SCIELO) electronic library,, from 1998 to 2018, using descriptors to search for data in Portuguese, English and Spanish. The sample consisted of 20 articles, with predominance of the English language, prospective studies and carried out in developing countries. The concept and criteria for the classification of neonatal near miss are still under construction, but advances in their use have been described. Although there is no consensus on the use of neonatal near miss, it is considered an auspicious tool to monitor and avoid the “accident / near death” in the neonatal period and make it possible to assess the quality of care.